Classical Notions of Coagulation Revisited in Relation with Blood Losses, Transfusion Rate for 700 Consecutive Liver Transplantations - Massicotte, Luc; Thibeault, Lynda; Roy, André (Seminars in Thrombosis and Hemostasis, 2015)
During the last decade, improved surgical and anesthetic management, such as better understanding of coagulation defects and the use of the phlebotomy, has reduced intraoperative blood product transfusions during orthotopic liver transplantation (OLT). The goal of this study was to look at the impact of initial conventional coagulation tests on blood loss and blood product requirement and to evaluate the role of the phlebotomy during liver transplantations. A total of 700 consecutive OLTs were studied. The group of patients was split into two according to the median of starting international normalized ratio to study blood losses and transfusion rate. Logistic regression was used to determine the main predictors of blood loss, intraoperative blood transfusion, and survival. There was no intergroup difference for demographic characteristics. The mean blood loss was 1,184 mL with a median of 920 mL. Overall, 77.4% of the patients did not receive any blood product and the mean transfusion rate of red blood cells (RBCs) was 0.5 ± 1.4 units per patient. Severity of recipients' disease did not correlate with blood loss or transfusion rate. Starting hemoglobin value was the only biochemical variable linked to RBC transfusions. Phlebotomy was linked to decrease in blood loss, RBC transfusions, and increased survival rate. It is concluded that bleeding did not correlate with traditional coagulation defects or the severity of recipient's disease. Preemptive phlebotomy was linked to a decreased blood loss, a decreased transfusion rate, and an increased 1-year survival rate.
Keywords: liver transplantation; coagulation; transfusion; phlebotomy; antifibrinolytic; cell saver; MELD score